Pilgrim Coaches: a New Phenomenon - Munro, Dane (The international journal of religious tourism and pilgrimage, 2021)
This article introduces the relatively new phenomenon of the pilgrim coach, i.e. a recently developed profession whose practitioners help people along the mental trajectory of pilgrimhood. Historically, the pilgrim was subject to "codified forms which governed conduct, termination, and purpose" (Gros, 2015:107). Pilgrims were instructed by their local church how they best could fulfil their vows along the way and at the shrines. In the post-pilgrimage era (Munro, 2017), where tourism is integrated with pilgrimage, new pilgrim routes are being created for both the religious and non-religious for the purpose of connecting people to a goal or philosophy through pilgrimage. In Belgium and the Netherlands, the profession of walking coach or nature coach has become popular in the last ten to fifteen years, and accredited courses have emerged. The aim is to re-acquaint people with nature's stress-relieving and health-bringing effects. Pilgrimage coaching is then a natural specialisation in this profession, offering nature coaching knowledge, supplemented with other academic disciplines added to the package to pilgrims, people who walk through nature with an added purpose. This article discusses new, circular pilgrim routes, and concentrates mainly on the Walk of Wisdom in the Netherlands. This route was initiated as a non-religious but spiritually-rich circular pilgrim route, driven by environmental sustainability, while simultaneously providing the services of professional pilgrim coaches. Besides confirming the benefits of pilgrimage as we know it, the pilgrim coach also offers new insights in the psychology and therapeutic values of pilgrimage.